PENGARUH DEBT TOTAL ASSET RATIO, CASH RATIO (CR), EARNING PER SHARE, DAN ASSET GROWTH TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2013 – 2017 - Cheria Tandiono; Devi Gunawan; Angel Angel; Friska Darnawaty Sitorus; Tantri Octora; Dwi Syah Putri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The ratio of Total Assets, Cash Ratio, Per Share Income and Asset Growth to Dividend Payment Ratios in consumer goods industry sector companies listed on the Indonesia Stock Exchange. The number of samples taken in this study were 12 companies. Determination of samples in this study using purposive sampling. This study uses a multiple linear regression analysis method assisted by the SPSS program. Based on the results of the data processing, it was obtained that the Total Asset Debt Ratio was received negatively and significantly to the Dividend Payment Ratio. The cash ratio is negative and significant to the Dividend Payment Ratio. Earnings Per Share has a positive and significant effect on the Dividend Payment Ratio. Asset Growth has a negative and significant effect on Payment Dividend Ratio. The expected results are significant coefficient of determination (R2) of 0.396, this means that 39.6 percent of the variation in dividends Payment ratios are reviewed by the Total Debt Asset Ratio, Cash Ratio, Earnings Per Share and Asset Growth by 60.4 percent by other model variables